The use of symptomatic slow-acting drugs for osteoarthritis of the joints of the hands: Accent on microcirculation parameters - A. S. Trofimova; V. I. Mazurov; A. A. Shokhin; E. A. Trofimov (Научно-практическая ревматология, 2024)
The aim of the study – to evaluate the effectiveness of the drug Alflutop (bioactive concentrate of small marine fish), as well as its effect on microcirculation parameters in patients with osteoarthritis (OA) of small joints of the hands.Patients and methods. The study included 80 patients aged 35 to 65 years with OA of small joints of the hands, stage I– II according to Kellgren – Lawrence, with pain ≥40 mm and ≤90 mm on a visual analogue scale (VAS). Subjects were distributed in 1:1 ratio. In the study group (combined therapy) patients received Alflutop according to the standard scheme: 2 ml intramuscularly every other day N 10 and meloxicam 7.5–15 mg per day in the “on demand” mode. The second group (monotherapy) received meloxicam 7.5–15 mg per day N 20. During the observation, the dynamics of joint pain on the VAS scale, the dynamics of the disease on the VAS scale by the patient and the doctor, the functional Dreiser index and AUSCAN (Australian/Canadian Osteoarthritis Hand Index), nailfold capillaroscopy (NFC) with an assessment of the number of capillaries and the number of alterations per 1 mm of the distal row of capillaries were evaluated. The duration of the study was 6 weeks.Results and discussion. By the 35th day of treatment with Alflutop in combination with meloxicam, a statistically significant decrease in pain and functional activity of the disease was found according to the VAS indices, the AUSCAN index (p<0.05) compared with the meloxicam monotherapy group. Microcirculation parameters according to NFC data in the Alflutop and meloxicam group remained stable by the end of the study (p>0.05). In meloxicam monotherapy group, by the 35th day of follow-up, there was a significant increase in the number of altered capillaries by 1 mm of the distal row of the nail (p<0.001).Thus, Alflutop demonstrates clinical efficacy in OA of the joints of the hands (reduces pain, stiffness, improves joint function). In addition, the effect of Alflutop with respect to slowing down microcirculatory disorders is not excluded.